Security Analysis of BigBlueButton and eduMEET - Heitmann, Nico; Siewert, Hendrik; Moog, Sven; Somorovsky, Juraj (Applied Cryptography and Network Security)
Video conferencing systems have become an indispensable part of our world. Using video conferencing systems implies the expectation that online meetings run as smoothly as in-person meetings. Thus, online meetings need to be just as secure and private as in-person meetings, which are secured against disruptive factors and unauthorized persons by physical access control mechanisms. To show the security dangers of conferencing systems and raise general awareness when using these technologies, we analyze the security of two widely used research and education open-source video conferencing systems: BigBlueButton and eduMEET. Because both systems are very different, we analyzed their architectures, considering the respective components with their main tasks, features, and user roles. In the following systematic security analyses, we found 50 vulnerabilities. These include broken access control, NoSQL injection, and denial of service (DoS). The vulnerabilities have root causes of different natures. While BigBlueButton has a lot of complexity due to many components, eduMEET, which is relatively young, focuses more on features than security. The sheer amount of results and the lack of prior work indicate a research gap that needs to be closed since video conferencing systems continue to play a significant role in research, education, and everyday life.

Isolating Personal Knowledge Spillovers: Coinventor Deaths and Spatial Citation Differentials - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (American Economic Review: Insights)
We propose a new method to estimate and isolate the localization of knowledge spillovers due to the physical presence of a person, using after-application but pre-grant deaths of differently located coinventors of the same patent. The approach estimates the differences in local citations between the deceased and still-living inventors at increasingly distant radii. Patents receive 26 percent fewer citations from within a radius of 20 miles around the deceased, relative to still-living coinventors. Differences attenuate with time and distance, are stronger when still-living coinventors live farther from the deceased, and hold for a subsample of possibly premature deaths. (JEL O31, O33, O34, R32)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Technology and Civic Virtue - Reijers, Wessel (Philosophy & Technology)
Abstract Today, a major technological trend is the increasing focus on the person: technical systems personalize, customize, and tailor to the person in both beneficial and troubling ways. This trend has moved beyond the realm of commerce and has become a matter of public governance, where systems for citizen risk scoring, predictive policing, and social credit scores proliferate. What these systems have in common is that they may target the person and her ethical and political dispositions, her virtues. Virtue ethics is the most appropriate approach for evaluating the impacts of these new systems, which has translated in a revival of talk about virtue in technology ethics. Yet, the focus on individual dispositions has rightly been criticized for lacking a concern with the political collective and institutional structures. This paper advocates a new direction of research into civic virtue, which is situated in between personal dispositions and structures of governance. First, it surveys the discourse on virtue ethics of technology, emphasizing its neglect of the political dimension of impacts of emerging technologies. Second, it presents a pluralist conception of civic virtue that enables us to scrutinize the impact of technology on civic virtue on three different levels of reciprocal reputation building, the cultivation of internal goods, and excellence in the public sphere. Third, it illustrates the benefits of this conceptions by discussing some paradigmatic examples of emerging technologies that aim to cultivate civic virtue.
Keywords: History and Philosophy of Science; Philosophy

Who Will Own Our Global Digital Twin: The Power of Genetic and Biographic Information to Shape Our Lives - Hellweg, Talea Davina; Schneider, Martin; Rückert, Ulrich; Harteis, Christian; Pilz, Sarah (The Digital Twin of Human)
Today, it is possible to collect and connect large amounts of digital data from various sources and life domains. This chapter examines the potential and the risks of this development from an interdisciplinary perspective. It defines the ‘global digital twin’ of a human being as the sum of all digitally stored information and predictive knowledge about a person. It points out that, compared to the digital twin of a machine, the human global digital twin is far more complex because it comprises the genetic code and the biographic code of a person. The genetic code contains not only a simple ‘construction plan’ but also hereditary information, in a form that is difficult to read. The biographic code contains all other information that can be assembled about a person, which is obtained via data from cameras, microphones, or other sensors, as well as general personal information. When the growing wealth of information concerning the genetic code and the biographical code is properly utilised, insights from biology and the behavioural sciences may be used to predict personal events such as health problems, job resignations, or even crimes. Because our own interests and those of private firms are partly in conflict over the use of this powerful knowledge, it is still unclear whether the global digital twins of humans will become a liberating or disciplining force for citizens. On the one hand, human beings are not machines: They are aware of their digital twin and therefore are able to influence it throughout their lives. Because of their free will, human beings are in general difficult to predict. Dystopias of full control over individual behaviour are therefore unlikely to materialise. On the other hand, private firms are beginning to take advantage of the available digital twins of humans by monopolising data access and by commercialising predictive knowledge. This is problematic because, unlike machines, human beings cannot only benefit from but also suffer due to their digital twins as they attempt to shape their own lives. We illustrate these issues with some examples and arrive at two conclusions: It is in the public interest for people to be granted more property rights over their personal global digital twins, and publicly funded research needs to become more interdisciplinary, much like private firms that have already begun to perform interdisciplinary research.

On the Multimodal Resolution of a Search Sequence in Virtual Reality - Klowait, Nils (Human Behavior and Emerging Technologies)
In virtual reality (VR), participants may not always have hands, bodies, eyes, or even voices—using VR helmets and two controllers, participants control an avatar through virtual worlds that do not necessarily obey familiar laws of physics; moreover, the avatar’s bodily characteristics may not neatly match our bodies in the physical world. Despite these limitations and specificities, humans get things done through collaboration and the creative use of the environment. While multiuser interactive VR is attracting greater numbers of participants, there are currently few attempts to analyze the in situ interaction systematically. This paper proposes a video-analytic detail-oriented methodological framework for studying virtual reality interaction. Using multimodal conversation analysis, the paper investigates a nonverbal, embodied, two-person interaction: two players in a survival game strive to gesturally resolve a misunderstanding regarding an in-game mechanic—however, both of their microphones are turned off for the duration of play. The players’ inability to resort to complex language to resolve this issue results in a dense sequence of back-and-forth activity involving gestures, object manipulation, gaze, and body work. Most crucially, timing and modified repetitions of previously produced actions turn out to be the key to overcome both technical and communicative challenges. The paper analyzes these action sequences, demonstrates how they generate intended outcomes, and proposes a vocabulary to speak about these types of interaction more generally. The findings demonstrate the viability of multimodal analysis of VR interaction, shed light on unique challenges of analyzing interaction in virtual reality, and generate broader methodological insights about the study of nonverbal action.
Keywords: Human-Computer Interaction; General Social Sciences; Social Psychology; Virtual Reality : Multimodality; Nonverbal Interaction; Search Sequence; Gesture; Co-Operative Action; Goodwin; Ethnomethodology

Distortion through modeling asymmetric bargaining power - Haake, Claus-Jochen; Streck, Thomas
We study the consequences of modeling asymmetric bargaining power in two-person bargaining problems. Comparing application of an asymmetric version of a bargaining solution to an upfront modification of the disagreement point, the resulting distortion crucially depends on the bargaining solution concept. While for the Kalai-Smorodinsky solution weaker players benefit from modifying the disagreement point, the situation is reversed for the Nash bargaining solution. There, weaker players are better off in the asymmetric bargaining solution. When comparing application of the asymmetric versions of the Nash and the Kalai-Smorodinsky solutions, we demonstrate that there is an upper bound for the weight of a player, so that she is better off with the Nash bargaining solution. This threshold is ultimately determined by the relative utilitarian bargaining solution. From a mechanism design perspective, our results provide valuable information for a social planner, when implementing a bargaining solution for unequally powerful players.
Keywords: Asymmetric bargaining power; Nash bargaining solution; Kalai-Smorodinsky bargaining solution

Exploration of Location Data: Real Data in the Context of Interaction with a Cellular Network - Höper, Lukas; Podworny, Susanne; Schulte, Carsten; Frischemeier, Daniel (Proceedings of the IASE 2021 Satellite Conference)
Students are not aware and have little understanding of collecting and processing personal data in their everyday contexts of interaction with data-driven digital artifacts. To be aware of where, how and why data are collected and processed is important to be self-determined. Therefore, we develop and evaluate a teaching sequence to provide reasoning about data as a fundamental aspect of statistical literacy. This teaching sequences deals with the context of interaction with a cellular network where location data are collected. Students get real location data from an unknown person which can be explored with the aim to characterize the person. Students gain different insights by using different basic filters and explain how they achieve these. The results of the exploratory study indicate that students learned to gain insights by exploring given location data and that these insights may describe the person with detailed aspects that may not necessarily be true.

Boosting artificial intelligence in design processes by the use of additive manufacturing - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Proceedings of the 33rd Annual International Solid Freeform Fabrication Symposium 2022)
Additive manufacturing offers the option of converting digital prototypes into real structures as quickly as possible by the special property of tool-free manufacturing. However, this process can only be used at optimum speed if bottlenecks can be effectively avoided. One of these constraints is the design process. Although modern CAD systems allow a significant increase in many areas, this always requires a person with specific skills (e.g. engineer). In the field of AM in particular, more and more powerful software solutions have recently been published which accelerate the Design for Additive Manufacturing, including most CAD-tasks. In many areas, therefore, attempts are already made to automate relevant design steps as much as possible, more and more using neural networks and artificial intelligence. This paper presents how and why such techniques can be used to generate three-dimensional structures quickly and efficiently in cases of deep generative design tasks.

The broken chain: Evidence against emotionally driven upstream indirect reciprocity - Schnedler, Wendelin (Games and Economic Behavior)
Psychologists claim that being treated kindly puts individuals in a positive emotional state: they then treat an unrelated third party more kindly. Numerous experiments document that subjects indeed ‘pay forward’ specific behavior. For example, they are less generous after having experienced stinginess. This, however, is not necessarily driven by emotions. Subjects may also imitate what they regard as socially adequate behavior. Here, I present an experiment in which imitation is not possible at the next opportunity to act with a stranger: after being given either a fun or an annoying job, subjects have to decide whether to be generous or not. I find that although subjects who are given the annoying job report more negative emotions than those with the fun job, they do not treat an unrelated third person more unkindly in terms of passing on less money.
Keywords: Economics and Econometrics; Finance

Vertrauen im Sport – mehr als nur ein No-Look-Pass - Meier, Heiko (Facetten des Vertrauens und Misstrauens)
Ohne ständig thematisiert zu werden, kommt Vertrauen im Sport immer eine große Bedeutung zu, sei es beim No-look-Pass, bei der Hilfestellung im Turnen oder im Klettersport. Mehr noch: Ohne Vertrauensgrundlage ist Sport praktisch oftmals unmöglich. Umgekehrt wiegen Vertrauensbrüche schwer. Sie gefährden Sportarten, Sportorganisationen und Personen. Damit ist der Aufbau von Vertrauen offensichtlich für den Sport konstitutiv. Der Beitrag untersucht deshalb, wie Vertrauen im Sport nicht nur soziale Verhältnisse und Beziehungen umrahmt, sondern sie konstituiert, und inwiefern sich der Sport diesbezüglich von anderen gesellschaftlichen Kontexten unterscheidet. Dazu wird unter Rückgriff auf Niklas Luhmanns Unterscheidung zwischen Person- und Systemvertrauen der Sportverein dahingehend analysiert, wie bedeutsam und wie funktional Vertrauen für dessen Selbstorganisation und Systemerhalt ist. Dies führt zu dem Vorschlag, Vertrauen im Sportverein als Steuerungsinstrument anzusehen, welches in einer spezifischen Symbolik zum Ausdruck kommt.

Immersive augmented reality system for the training of pattern classification control with a myoelectric prosthesis - Boschmann, Alexander; Neuhaus, Dorothee; Vogt, Sarah; Kaltschmidt, Christian; Platzner, Marco; Dosen, Strahinja (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Hand amputation can have a truly debilitating impact on the life of the affected person. A multifunctional myoelectric prosthesis controlled using pattern classification can be used to restore some of the lost motor abilities. However, learning to control an advanced prosthesis can be a challenging task, but virtual and augmented reality (AR) provide means to create an engaging and motivating training. Methods In this study, we present a novel training framework that integrates virtual elements within a real scene (AR) while allowing the view from the first-person perspective. The framework was evaluated in 13 able-bodied subjects and a limb-deficient person divided into intervention (IG) and control (CG) groups. The IG received training by performing simulated clothespin task and both groups conducted a pre- and posttest with a real prosthesis. When training with the AR, the subjects received visual feedback on the generated grasping force. The main outcome measure was the number of pins that were successfully transferred within 20 min (task duration), while the number of dropped and broken pins were also registered. The participants were asked to score the difficulty of the real task (posttest), fun-factor and motivation, as well as the utility of the feedback. Results The performance (median/interquartile range) consistently increased during the training sessions (4/3 to 22/4). While the results were similar for the two groups in the pretest, the performance improved in the posttest only in IG. In addition, the subjects in IG transferred significantly more pins (28/10.5 versus 14.5/11), and dropped (1/2.5 versus 3.5/2) and broke (5/3.8 versus 14.5/9) significantly fewer pins in the posttest compared to CG. The participants in IG assigned (mean ± std) significantly lower scores to the difficulty compared to CG (5.2 ± 1.9 versus 7.1 ± 0.9), and they highly rated the fun factor (8.7 ± 1.3) and usefulness of feedback (8.5 ± 1.7). Conclusion The results demonstrated that the proposed AR system allows for the transfer of skills from the simulated to the real task while providing a positive user experience. The present study demonstrates the effectiveness and flexibility of the proposed AR framework. Importantly, the developed system is open source and available for download and further development.

Understanding Collaboration with Virtual Assistants – The Role of Social Identity and the Extended Self - Mirbabaie, Milad; Stieglitz, Stefan; Brünker, Felix; Hofeditz, Lennart; Ross, Björn; Frick, Nicholas R. J. (Business & Information Systems Engineering)
Abstract Organizations introduce virtual assistants (VAs) to support employees with work-related tasks. VAs can increase the success of teamwork and thus become an integral part of the daily work life. However, the effect of VAs on virtual teams remains unclear. While social identity theory describes the identification of employees with team members and the continued existence of a group identity, the concept of the extended self refers to the incorporation of possessions into one’s sense of self. This raises the question of which approach applies to VAs as teammates. The article extends the IS literature by examining the impact of VAs on individuals and teams and updates the knowledge on social identity and the extended self by deploying VAs in a collaborative setting. Using a laboratory experiment with N = 50, two groups were compared in solving a task, where one group was assisted by a VA, while the other was supported by a person. Results highlight that employees who identify VAs as part of their extended self are more likely to identify with team members and vice versa. The two aspects are thus combined into the proposed construct of virtually extended identification explaining the relationships of collaboration with VAs. This study contributes to the understanding on the influence of the extended self and social identity on collaboration with VAs. Practitioners are able to assess how VAs improve collaboration and teamwork in mixed teams in organizations.

Immersive augmented reality system for the training of pattern classification control with a myoelectric prosthesis - Boschmann, Alexander; Neuhaus, Dorothee; Vogt, Sarah; Kaltschmidt, Christian; Platzner, Marco; Dosen, Strahinja (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Hand amputation can have a truly debilitating impact on the life of the affected person. A multifunctional myoelectric prosthesis controlled using pattern classification can be used to restore some of the lost motor abilities. However, learning to control an advanced prosthesis can be a challenging task, but virtual and augmented reality (AR) provide means to create an engaging and motivating training. Methods In this study, we present a novel training framework that integrates virtual elements within a real scene (AR) while allowing the view from the first-person perspective. The framework was evaluated in 13 able-bodied subjects and a limb-deficient person divided into intervention (IG) and control (CG) groups. The IG received training by performing simulated clothespin task and both groups conducted a pre- and posttest with a real prosthesis. When training with the AR, the subjects received visual feedback on the generated grasping force. The main outcome measure was the number of pins that were successfully transferred within 20 min (task duration), while the number of dropped and broken pins were also registered. The participants were asked to score the difficulty of the real task (posttest), fun-factor and motivation, as well as the utility of the feedback. Results The performance (median/interquartile range) consistently increased during the training sessions (4/3 to 22/4). While the results were similar for the two groups in the pretest, the performance improved in the posttest only in IG. In addition, the subjects in IG transferred significantly more pins (28/10.5 versus 14.5/11), and dropped (1/2.5 versus 3.5/2) and broke (5/3.8 versus 14.5/9) significantly fewer pins in the posttest compared to CG. The participants in IG assigned (mean ± std) significantly lower scores to the difficulty compared to CG (5.2 ± 1.9 versus 7.1 ± 0.9), and they highly rated the fun factor (8.7 ± 1.3) and usefulness of feedback (8.5 ± 1.7). Conclusion The results demonstrated that the proposed AR system allows for the transfer of skills from the simulated to the real task while providing a positive user experience. The present study demonstrates the effectiveness and flexibility of the proposed AR framework. Importantly, the developed system is open source and available for download and further development.
Keywords: Health Informatics; Rehabilitation

Socio-legal systems and implementation of the Nash solution in Debreu–Hurwicz equilibrium - Haake, Claus-Jochen; Trockel, Walter (Review of Economic Design)
Abstract In this article we combine Debreu’s (Proc Natl Acad Sci 38(10):886–893, 1952) social system with Hurwicz’s (Econ Design 1(1):1–14, 1994; Am Econ Rev 98(3):577–585, 2008) ideas of embedding a “desired” game form into a “natural” game form that includes all feasible behavior, even if it is “illegal” according to the desired form. For the resulting socio-legal system we extend Debreu’s concepts of a social system and its social equilibria to a socio-legal system with its Debreu–Hurwicz equilibria. We build on a more general version of social equilibrium due to Shafer and Sonnenschein (J Math Econ 2(3):345–348, 1975) that also generalizes the dc-mechanism of Koray and Yildiz (J Econ Theory 176:479–502, 2018) which relates implementation via mechanisms with implementation via rights structures as introduced by Sertel (Designing rights: invisible hand theorems, covering and membership. Tech. rep. Mimeo, Bogazici University, 2001). In the second part we apply and illustrate these new concepts via an application in the narrow welfarist framework of two person cooperative bargaining. There we provide in a socio-legal system based on Nash’s demand game an implementation of the Nash bargaining solution in Debreu–Hurwicz equilibrium.

Testing as an approach to control the Corona epidemic dynamics and avoid lockdowns - Gries, Thomas; Welfens, Paul J. J. (International Economics and Economic Policy)
Abstract Vaccinations, lockdowns and testing strategies are three potential elements of an effective anti-coronavirus, and in particular Covid-19, health policy. The following analysis considers - within a simple model - the potentially crucial role of a Corona testing approach in combination with a quarantine approach which is shown herein to be a substitute for broad lockdown measures. The cost of lockdowns/shutdowns are rather high so that – beyond progress in terms of a broad vaccination program – a rational testing strategy should also be carefully considered. Testing has to be organized on the basis of an adequate testing infrastructure which could largely be implemented in firms, schools, universities and public administration settings. As regards the cost of a systematic broad Covid-19 testing strategy, these could come close to 0.5% of national income if there are no vaccinations. The Testing & Quarantine approach suggested here – with tests for symptomatic as well as asymptomatic people - is based on a random sampling and would require rather broad and frequent testing; possibly one test per person every 7–10 days. At the same time, one should consider that the cost of further lockdowns/shutdowns of a duration of 1 month could be very high, such that a standard cost benefit analysis supports the testing approach suggested herein. Also, an optimal policy mix could be designed where both vaccinations and testing play a crucial role. As of late January 2021, no further lockdowns in Germany and other OECD countries would be necessary if a broad testing infrastructure can be established rather quickly. This in turn will reinforce economic optimism and help to jumpstart economic growth in Europe, the US and Asia in a solid way. The basic logic of the testing approach pointed out here for industrialized countries could also be applied in developing countries. The approach presented is complementary to the IMF analysis of Cherif/Hasanov.
Keywords: Economics and Econometrics

When agency “fits” regardless of gender: Perceptions of applicant fit when job and organization signal male stereotypes - Dutz, Regina; Hubner-Benz, Sylvia; Peus, Claudia (Personnel Psychology)
Evaluators’ fit assessments are not only influenced by applicants’ qualities, but also by stereotypes, especially in recruitment for high‐status jobs in male‐dominated fields. The unidimensional agentic stereotype of these work contexts signals agentic job and organizational requirements (stereotypically male qualities such as achievement orientation), although the actual requirements usually also include communality (stereotypically female qualities such as interpersonal skills). In five experiments, we investigate the relevance of perceived applicant agency for perceived applicant fit, the influence of recruitment material, contextual differences, and the role of applicant gender. Our findings indicate that perceived applicant agency drives perceived person‐job and person‐organization fit in strictly male stereotyped work contexts, regardless of gender, and agentic recruitment material enhances this effect. Contrasting different contexts (high‐ with low‐status jobs and a male‐dominated with a gender‐balanced and female‐dominated field) revealed that the relevance of perceived agency increases with perceived job status, and the relevance of perceived communality decreases with the expected share of men. Although women were perceived as highly agentic in strictly male stereotyped work contexts, their need to be perceived as agentic also was higher than for men, due to the perceived lack of fit between women and high‐status jobs.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology

The interplay of personal and contextual diversity during the first year at Higher Education: Combining a quantitative and a qualitative approach - Jenert, Tobias; Brahm, Taiga (Frontline Learning Research)
Research on student transition into Higher Education (HE) has taken different theoretical perspectives. First, studies investigated personal variables such as students´ self-efficacy, emotions and motivation regarding the transition from school to HE. A second strand of research focused on contextual variables, for instance college effectiveness research. With this paper, we combine both the personal and the contextual approach. We aim to investigate the interaction between personal and contextual diversity during the transition into HE, taking into account students’ diversity in particular with regard to gender and individual characteristics, such as self-efficacy. We explored the heterogeneity in students’ personal characteristics by conducting a latent profile analysis (LPA) based on students’ intrinsic motivation, self-efficacy and anxiety before entering Higher Education. LPA resulted in three distinct profiles, with significant differences in how students perceived the first year. This finding suggests that students’ personal characteristics when entering Higher Education influence how they experience the study environment. To investigate the interplay between individual and contextual differences in more detail, we conducted a qualitative longitudinal study with 14 first-year students in parallel with the panel survey. We found that individual students react very differently to specific characteristics and events of the first-year environment. Our study adds to the growing body of research that aims to grasp the complexity of interactions between individual and contextual differences. Specifically, we illustrate how combining quantitative and qualitative methods can provide new insights into person-context interactions.
Keywords: Education

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Adipöse Personen im Feuerwehreinsatz - Wolff, Jens
Einsätze mit adipösen Personen stellen die Feuerwehr und den Rettungsdienst vor vielfältige Herausforderungen, da Rettung und Transport für die Einsatzkräfte eine logistische Hürde mit Mehraufwand und Risiken darstellen. Der Autor untersucht die Besonderheiten bei bestimmten Einsatzszenarien; angefangen bei der Trageunterstützung für den Rettungsdienst über den Verkehrsunfall mit eingeklemmter adipöser Person bis hin zum Brandeinsatz mit schwergewichtigen Menschen. Mögliche Einsätze werden abgegrenzt und etwaige Besonderheiten im Vergleich zu den üblichen "Standardeinsätzen" diskutiert. Einblicke in rettungsdienstliche Aspekte bei Einsätzen mit adipösen Patientinnen und Patienten vervollständigen das Buch.

Gattung, Gender, Gesang. Neue Forschungsperspektiven auf Hans Werner Henzes Werk
Hans Werner Henze (1926–2012) gilt als einer der bedeutendsten deutschen Opernkomponisten der Gegenwart. Der vorliegende Band vereinigt die Ergebnisse zweier wissenschaftlicher Tagungen, die sich gleichermaßen der Person und dem Werk Henzes verpflichtet fühlten. Ein Schwerpunkt liegt auf Texten zu seiner 1983 uraufgeführten »Geschichte für Sänger und Instrumentalisten« Die Englische Katze. In Abbildungen und Transkriptionen öffentlicher Diskussionen wird dabei unter anderem das Inszenierungskonzept der Staatsoper Hannover in der Spielzeit 2016/2017 dokumentiert. Zudem beschäftigt sich der Band mit dem Rückbezug Henzes auf unterschiedliche Traditionen sowie mit seinem Schüler Detlev Glanert, der in seinem Musiktheater gleichfalls der Idee eines modernen Humanismus verpflichtet ist. Eine Würdigung von Henzes hochaktuellem Gesamtwerk steht bis heute noch aus.

Kritisch-reflexive Praxiserfahrungen in der Grundschule: Das Projekt "Schule für alle" - Pieper, Catania; Kottmann, Brigitte; Miller, Susanne (System. Wandel. Entwicklung. Akteurinnen und Akteure inklusive Prozesse im Spannungsfeld von Institution, Profession und Person)

“As a person, I feel I’ve changed pretty immensely”: Sojourners’ aspirations and self-perceived achievements - Müller, Mareike (The Canadian Modern Language Review)
This article explores the interplay between learners’ linguistic and personal objectives as well as evaluations of their achievements in study-abroad contexts, an area that has thus far remained widely unexplored given the prevalence of product-oriented, outcomes-based research. The study draws on the case of one Canadian student of German who studied abroad at a German university for one year. To adopt an emic perspective, the data gained from a learning history questionnaire, semi-structured interviews, and e-journals were analyzed and interpreted within the framework of narrative analysis. The results show not only that learners’ sojourn objectives may be complex, dynamic, and contradictory in nature but also that they need to be examined beyond their face value, as they are entangled with learners’ negotiations of desirable subject positions and attempts to integrate their sojourn experiences, successes, and frustrations in a coherent and positive life narrative.
Keywords: individual differences; learner beliefs; narrative analysis; sojourn objectives and evaluations; study abroad

The interplay between subjective abilities and subjective demands and its relationship with academic success. An application of the person–environment fit theory - Bohndick, Carla; Rosman, Tom; Kohlmeyer, Susanne; Buhl, Heike M. (Higher Education)
In this study, we draw on person–environment fit theory to analyze whether academic success is best explained by individual abilities subjectively exceeding situational demands or by abilities matching the demands. Moreover, we disentangled effects of perceived abilities and subjective person–environment (P-E) fit on academic success. All in all, 693 teacher education students participated in an online questionnaire. Students were asked to rate general requirements of their academic programs (e.g., self-discipline) on a 5-point scale in terms of (1) their own abilities and (2) the perceived relevance for their studies. P-E fit was determined by difference scores between abilities and relevance ratings. Academic success was assessed by grades, perceived performance, and study satisfaction. Data were analyzed through structural equation modeling and suggest that academic success is best explained by a match between abilities and demands. Moreover, all three criteria for academic success were more strongly related to subjective fit than to subjective abilities.
Keywords: Academic success; Person–environment fit theory; Demands–abilities fit; Higher education

Reconsidering Second-Person Narration and Involvement - Mildorf, Jarmila (Language and Literature)

A System for Uncovering Latent Connectivity of Health Care Providers in Online Reviews - Bäumer, Frederik Simon; Geierhos, Michaela; Schulze, Sabine (Information and Software Technologies. 21st International Conference, ICIST 2015, Druskininkai, Lithuania, October 15-16, 2015. Proceedings)
The contacts a health care provider (HCP), like a physician, has to other HCPs is perceived as a quality characteristic by patients. So far, only the German physician rating website jameda.de gives information about the interconnectedness of HCPs in business networks. However, this network has to be maintained manually and is thus incomplete. We therefore developed a system for uncovering latent connectivity of HCPs in online reviews to provide users with more valuable information about their HCPs. The overall goal of this approach is to extend already existing business networks of HCPs by integrating connections that are newly discovered by our system. Our most recent evaluation results are promising: 70.8 % of the connections extracted from the reviews texts were correctly identified and in total 3,788 relations were recognized that have not been displayed in jameda.de’s network before.
Keywords: Latent Connectivity; Person Named Entity Recognition and Disambiguation; Health Care Provider Reviews

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

„Ich muss mal um Rat/Bestätigung/kollektives Aufregen bitten“ – Kommunikations(t)räume für Lehrkräfte - Jahn, Robert W.; Goller, Michael (Lernräume: Gestaltung von Lernumgebungen für die Weiterbildung)
Die Diskussionen um pädagogische Professionalität thematisieren die Bedeutung innerprofessioneller Kooperations- und Kommunikationsprozesse aus verschiedenen Blickwinkeln. HELSPER weist auf den ausgleichenden Umgang mit antinomischen, unvereinbaren Handlungsdilemmata hin, in die Lehrer involviert seien und die nur reflexiv bearbeitet werden können – wobei es sowohl individueller als auch kollektiver Reflexionen bedarf. Nach BAUER handelt eine Person u.a. pädagogisch professionell, die sich mit anderen Angehörigen der Berufsgruppe verständigen kann. Im Allgemeinen kann festgehalten werden, dass die Reflexion von Anforderungen und Erfahrungen bei der professionellen beruflichen Entwicklung eine besondere Bedeutung besitzt.

'Unnatural’ Narratives? The Case of Second-Person Narration - Mildorf, Jarmila (The Travelling Concepts of Narrative)

Studying Writing in Second Person: A Response to Joshua Parker - Mildorf, Jarmila (Connotations: Journal for Critical Debate)

Customer Interaction Management goes Social: Getting Business Processes plugged in Social Networks - Geierhos, Michaela; Ebrahim, Mohamed (Computational Social Networks: Tools, Perspectives and Applications)
Within this chapter, we will describe a novel technical service dealing with the integration of social networking channels into existing business processes. Since many businesses are moving to online communities as a means of communicating directly with their customers, social media has to be explored as an additional communication channel between individuals and companies. While the English-speaking consumers on Facebook are more likely to respond to communication rather than to initiate communication with an organisation, some German companies already have regularly updated Facebook pages for customer service and support, e.g. Telekom. Therefore, the idea of classifying and evaluating public comments addressed to German companies is based on an existing demand. In order to maintain an active Facebook wall, the consumer posts have to be categorised and then automatically assigned to the corresponding business processes (e.g. the technical service, shipping, marketing, accounting, etc.). This service works like an issue tracking system sending e-mails to the corresponding person in charge of customer service and support. That way, business process management systems which are already used to e-mail communication can benefit from social media. This allows the company to follow general trends in customer opinions on the Internet; moreover it facilates the recording of two-sided communication for customer relationship management and the company’s response will be delivered through consumer’s preferred medium: Facebook.

Second-Person Narration in Literary and Conversational Storytelling - Mildorf, Jarmila (Storyworlds)

Dynamic pointing triggers shifts of visual attention in young infants - Rohlfing, Katharina; Longo, Matthew R.; Bertenthal, Bennett I. (Developmental Science)
Pointing, like eye gaze, is a deictic gesture that can be used to orient the attention of another person towards an object or an event. Previous research suggests that infants first begin to follow a pointing gesture between 10 and 13 months of age. We investigated whether sensitivity to pointing could be seen at younger ages employing a technique recently used to show early sensitivity to perceived eye gaze. Three experiments were conducted with 4.5- and 6.5-month-old infants. Our first goal was to examine whether these infants could show a systematic response to pointing by shifting their visual attention in the direction of a pointing gesture when we eliminated the difficulty of disengaging fixation from a pointing hand. The results from Experiments 1 and 2 suggest that a dynamic, but not a static, pointing gesture triggers shifts of visual attention in infants as young as 4.5 months of age. Our second goal was to clarify whether this response was based on sensitivity to the directional posture of the pointing hand, the motion of the pointing hand, or both. The results from Experiment 3 suggest that the direction of motion is necessary but not sufficient to orient infants’ attention toward a distal target. Infants shifted their attention in the direction of the pointing finger, but only when the hand was moving in the same direction. These results suggest that infants are prepared to orient to the distal referent of a pointing gesture which likely contributes to their learning the communicative function of pointing.

The Subject as Moral Person. On Husserl’s Late Reflections Concerning the Concept of Personhood - Luft, Sebastian (Investigating Subjectivity)

Prosopographie von Römischer Inquisition und Indexkongregation 1701-1813
Brennende Scheiterhaufen, Ketzerverfolgungen und verbotene Bücher – das gehört im landläufigen Bewusstsein zur Inquisition. Doch wie sieht es mit der historischen Wirklichkeit aus? In einem von der Deutschen Forschungsgemeinschaft geförderten, groß angelegten Forschungsprojekt wird eine Aufarbeitung der Geschichte der Buchzensur von Römischer Inquisition und Indexkongregation (1542 bis 1966) angegangen. Durch fundierte Archivstudien sowie durch akribische Detailarbeit gelingt es erstmals, die konkrete Arbeit beider Kongregationen zu dokumentieren. 2005 wurden die Bände für den Zeitraum 1814 bis 1917 präsentiert. Nun liegen für die Zeit von 1701 bis 1813 sechs weitere Bände vor. Alle in Rom verhandelten Bücher, egal aus welchem Wissens- und Wissenschaftsbereich, alle Gutachter und alle Urteile zur Buchzensur werden in einem interdisziplinär nutzbaren und international ausgerichteten Grundlagenwerk zugänglich gemacht. Die Prosopographie von Römischer Inquisition und Indexkongregation 1701 bis 1813 mit ihren etwa 1.000 bio-bibliographischen Einträgen zu den am Entscheidungsprozess der Kongregationen beteiligten Akteuren gibt den bislang anonymen Institutionen Inquisition und Indexkongregation ein konkretes Gesicht. Sie stellt einen einzigartigen Einblick in das „Innenleben“ von Römischer Inquisition und Indexkongregation dar. Biographisch Interessierten bietet sie vielfach nicht nur völlig unbekannte Lebens- und Karrieredaten und die gezielte Kompilation der wichtigsten Literatur, sondern dokumentiert auf breiter Quellenbasis die konkrete Gutachtertätigkeit der jeweiligen Person innerhalb der zwei Kongregationen. Diejenigen, die sich der Prosopographie über einen konkreten Zensurfall nähern, können mit ihrer Hilfe den häufig unbekannten Zensor identifizieren und sein Votum gezielt in den Kontext seiner gesamten Zensurtätigkeit einbetten. Kongregationsgeschichtlich schafft die Prosopographie schließlich einen Über- und Tiefenblick, der das Fundament für alle zukünftigen Studien und Forschunge über Römische Inquisition und Indexkongregation bilden wird.

Das Subjekt als moralische Person. Zu Husserls späten Reflexionen bezüglich des Personenbegriffs - Luft, Sebastian (Geist, Person, Gemeinschaft: Freiburger Beiträge zur Aktualität Husserls)
In this essay, I will attempt a systematic reconstruction of the general shape of Husserl’s late philosophy, insofar as it centers on the concept of personhood. The systematic concatenation of this and other themes in Husserl’s late work – the method of epoché and reduction, ethics, personhood, and teleology – has only recently begun to be explored in Husserl scholarship, and this article is a modest contribution to the further elucidation of their mutual relation-ship. One of the most striking results of this reconstructive analysis is Husserl’s final concept of “person“, which goes beyond the traditional distinctions, such as “heart“ and “mind“ or “reason“ and “emotion“. For Husserl to conceive of the subject as moral person implies, then, the demand to not only conduct oneself morally (in a novel sense of “moral”), but also to have an ethical view of the world as a world that bears meaning and harbors values despite its apparent absurdities.

Fusing Audio and Video Information for Online Speaker Diarization - Schmalenstroeer, Joerg; Kelling, Martin; Leutnant, Volker; Haeb-Umbach, Reinhold (Interspeech 2009)
In this paper we present a system for identifying and localizingspeakers using distant microphone arrays and a steerablepan-tilt-zoom camera. Audio and video streams are processedin real-time to obtain the diarization information grqqwho speakswhen and where'' with low latency to be used in advanced videoconferencing systems or user-adaptive interfaces. A key featureof the proposed system is to first glean information about thespeaker{\rq}s location and identity from the audio and visual datastreams separately and then to fuse these data in a probabilisticframework employing the Viterbi algorithm. Here, visual evidenceof a person is utilized through a priori state probabilities,while location and speaker change information are employedvia time-variant transition probablities. Experiments show thatvideo information yields a substantial improvement comparedto pure audio-based diarization.

Abstrakte Anerkennung. Über einen Fall misslungener Anerkennung beim frühen Hegel. - Ficara, Elena (Transzendentalphilosophie und Person)

A Low-Cost Positioning System for Location-Aware Applications in Smart Homes - Schäfer, Robbie; Müller, Wolfgang; Deimann, Roman; Kleinjohann, Bernd (Proceedings of the Workshop on Mobile Spatial Interaction at CHI 2007)
Location-aware services for private use such as GPS- based navigation systems and GSM-based offerings have become quite a success for outdoor applications, while indoor positioning systems are still mainly employed for professional use only. The main reasons are cost issues and the complexity of setup and maintenance of those systems. In this paper we present CaMPTrack (Camera-based Multiple Person Tracker), a prototype of a webcam-based positioning system and discuss its application and development challenges.
Keywords: Positioning Systems; Camera Based; Cost Efficiency; Smart Home Applications

„In diesem Schein des Bekannten liegt das ganze Geheimniß des Volkstons“ – Die Dichtung der Heidelberger Romantik in der Musik - Tumat, Antje (200 Jahre Heidelberger Romantik)
Die Dichtung der sogenannten „Heidelberger Romantik“ entfaltete ihre geistesgeschichtliche Wirkung in hohem Maße durch ihre musikalische Rezeption. Die Volksliedsammlung Des Knaben Wunderhorn 2 wurde von Achim von Arnim und Clemens Brentano ohne Notenbeigabe herausgegeben; bis ins 20. Jahrhundert reizten ihre Texte immer wieder zu Kompositionen, von denen die Wunderhorn-Lieder Gustav Mahlers heute die Bekanntesten sind.3 Die inhaltliche Heterogenität der Sammlung spiegelt sich in der Geschichte ihrer Vertonungen: Die verschiedenen Texte tragen einerseits Angebote zur kollektiven Identifikation, beispielsweise im nationalen Sinne, in sich. Gleichzeitig vermögen sie andererseits ein solches kollektives Identifikationsangebot zu durchkreuzen, indem sie das Leiden an der Außenseiterrolle — etwa in der Person eines Fahnenflüchtlings4 — thematisieren, wie in den von Gustav Mahler gewählten, zumeist von starker Gebrochenheit getragenen Liedern. Die Gestalt der Texte in der Sammlung sollte nach der Bearbeitung durch die beiden Herausgeber dem entsprechen, was sie unter „Volkston“ verstanden.5 Dieser „Ton“ der Texte wurde wiederum in der Folgezeit als verbürgter Volkston rezipiert. Er beeinflusste Dichter wie Joseph von Eichendorff, dessen Lyrik von der Wunderhorn-Sammlung inspiriert wurde.6 Das Heidelberger Jahr 1807/08, in dem dieser die Liedsammlung kennenlernte, war für Eichendorff „eines der entscheidendsten seines Lebens“.7 Die literarische Rezeption der Wunderhorn-Texte in seiner Lyrik fand wiederum ihrerseits in unzähligen Vertonungen musikalischen Widerhall, so etwa in Robert Schumanns Liederkreis op. 39.8

Register 1701-1813
Brennende Scheiterhaufen, Ketzerverfolgungen und verbotene Bücher – das gehört im landläufigen Bewusstsein zur Inquisition. Doch wie sieht es mit der historischen Wirklichkeit aus? In einem von der Deutschen Forschungsgemeinschaft geförderten, groß angelegten Forschungsprojekt wird eine Aufarbeitung der Geschichte der Buchzensur von Römischer Inquisition und Indexkongregation (1542 bis 1966) angegangen. Durch fundierte Archivstudien sowie durch akribische Detailarbeit gelingt es erstmals, die konkrete Arbeit beider Kongregationen zu dokumentieren. 2005 wurden die Bände für den Zeitraum 1814 bis 1917 präsentiert. Nun liegen für die Zeit von 1701 bis 1813 sechs weitere Bände vor. Alle in Rom verhandelten Bücher, egal aus welchem Wissens- und Wissenschaftsbereich, alle Gutachter und alle Urteile zur Buchzensur werden in einem interdisziplinär nutzbaren und international ausgerichteten Grundlagenwerk zugänglich gemacht. Einen Schlüssel zu den fünf Bänden liefert der Registerband. Er stellt die Verbindung zwischen den drei Säulen der Grundlagenforschung her. Die wichtigsten Informationen aus Systematischen Repertorium, Prosopographie und Bandi-Edition findet man hier in übersichtlicher Form zusammengefasst: Sitzungsdaten und verhandelte Werke, Zensoren und ihre Zensuren, Verbotsplakate und Archiv-Signaturen. Der Benutzer kann mit einem Blick erkennen, wer sich etwa mit welchem Buch beschäftigt hat oder wie vielfältig die Gutachtertätigkeit einer bestimmten Person war. Mit diesem wichtigen Hilfsmittel wird die Geschichte von Inquisition und Indexkongregation im 18. Jahrhundert erschlossen und für die weitere Forschung fruchtbar gemacht.

Bucket Game with Applications to Set Multicover and Dynamic Page Migration - Bienkowski, Marcin; Byrka, Jarosław (Proc. of the 13th Annual European Symposium on Algorithms (ESA 2005))
We present a simple two-person Bucket Game, based on throwing balls into buckets, and we discuss possible players' strategies. We use these strategies to create an approximation algorithm for a generalization of the well known Set Cover problem, where we need to cover each element by at least $k$ sets. Furthermore, we apply these strategies to construct a randomized algorithm for Dynamic Page Migration problem achieving the optimal competitive ratio against an oblivious adversary.

Influences of visibility, intentions, and probability in a peripheral cuing task. - Ansorge, Ulrich; Heumann, Manfred; Scharlau, Ingrid (Consciousness and Cognition: An International Journal)
According to the concept of direct parameter specification, nonconsciously registered information can be processed to the extent that it matches currently active intentions of a person. This prediction was tested and confirmed in the current study. Masked visual information provided by peripheral cues led to reaction time (RT) effects only if the information specified one of the required responses (Experiments 1 and 3). Information delivered by the same masked cues that did not match the intentions was not used. However, the same information influenced RT if it was provided by visible cues (Experiments 2 and 3). The results suggest that the processing of nonconsciously registered information is flexible because it is susceptible to the changing intentions of a person. Yet, these processes are apparently restricted as nonconsciously registered information cannot be used as easily for purposes not corresponding to the currently active intentions as better visible information. (PsycINFO
Keywords: active intentions; cues; direct parameter specification; nonconscious processing ability; Adult; Consciousness; Female; Humans; Male; Mental Processes; Perceptual Masking; Photic Stimulation; Visual Perception; Awareness; Cognitive Processes; Cues; Intention; Consciousness States; Probability